Method for producing polyimide film

In the process of manufacturing polyimide film, the diamine structural unit with a specific ionization potential and a multi-stage temperature-controlled imidation method are solved, and the film manufacturing with high colorless transparency, high elongation and excellent heat resistance is achieved.

CN119894963APending Publication Date: 2025-04-25MITSUBISHI GAS CHEM CO INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380065052.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the colorless transparency and high tensile elongation of the polyimide film under high temperature conditions, and it is also difficult to obtain a film with excellent heat resistance and low yellowness.

Method used

Full imidation and high molecular weighting of the polyimide precursor are achieved by removing solvent from the polyimide precursor varnish with a specific ionization potential and imidizing in stages at multiple temperatures.

Benefits of technology

The obtained polyimide film has high colorless transparency, high elongation and excellent heat resistance, and can maintain performance under high temperature conditions of 400°C or above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005304378700000031
    Figure BDA0005304378700000031
  • Figure BDA0005304378700000032
    Figure BDA0005304378700000032
  • Figure BDA0005304378700000033
    Figure BDA0005304378700000033
Patent Text Reader

Abstract

A method for producing a polyimide film, the method comprising: a step 1 in which a solvent is removed from a varnish containing a solvent and a polyimide precursor having a polyamic acid moiety at 50-120 DEG C, and the varnish is dried; and a step 2 in which the polyamic acid moiety has a structural unit derived from a tetracarboxylic acid dianhydride and a structural unit derived from a diamine, and the diamine that provides the structural unit derived from the diamine contains a diamine having an ionization potential of 7.10 eV or more, is held at 300-400 DEG C for 10-120 minutes and then held at 420-500 DEG C, thereby performing imidization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for producing a polyimide film. Background Art

[0002] Polyimide resins have been studied for various uses in the fields of electrical and electronic components. For example, in order to make devices lighter and more flexible, it is desired to replace glass substrates used in image display devices such as liquid crystal displays and OLED displays with plastic substrates, and research has been conducted on polyimide films suitable as such plastic substrates. Polyimide films for such uses are required to have various properties.

[0003] In response to such demands, for example, Patent Document 1 discloses a polyimide precursor characterized by containing two specific amic acid structural units at a specific ratio in order to obtain a polyimide film having low residual stress, little warpage, low yellowness, and high elongation.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2017 / 051827 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] As mentioned above, polyimide films for specific purposes are required to be colorless and transparent, have high tensile elongation, and have low residual stress. In particular, when the device type of TFT is LTPS (low temperature polycrystalline silicon TFT), the processing temperature exceeds 400°C, and the polyimide used as the substrate is required to be heat-resistant enough to withstand multiple treatments at high temperatures above 400°C, and to maintain colorless and transparent properties and high tensile elongation even in such a thermal history.

[0009] On the other hand, polyimide precursors undergo thermal imidization and increase in molecular weight during drying, thereby exhibiting high elongation and heat resistance. However, based on their characteristics, if the drying temperature and time are not adjusted properly, thermal imidization and increase in molecular weight may not proceed as expected, and the polyimide precursors may not be able to withstand the drying temperature, resulting in loss of transparency and tensile elongation.

[0010] Patent Document 1 discloses a technique for reducing residual stress and yellowness, but it is not sufficient as a method for stably producing such a polyimide film, and in particular, a polyimide film that maintains transparency and low yellowness and has excellent heat resistance has not yet been obtained.

[0011] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a method for producing a polyimide film, which can fully realize the imidization reaction and molecular weight increase of a polyimide precursor, and can obtain a polyimide film having high colorless transparency, high elongation and excellent heat resistance.

[0012] Solutions for solving problems

[0013] The present inventors have found that the above-mentioned problems can be solved by removing the solvent from a polyimide precursor varnish having a structural unit derived from a diamine having a specific ionization potential and performing imidization by stepwise holding at a plurality of temperatures, thereby completing the invention.

[0014] That is, the present invention relates to the following [1] to [9].

[0015] [1] A method for producing a polyimide film, comprising:

[0016] Step 1, removing the solvent from a varnish containing a polyimide precursor having a polyamic acid portion and a solvent at 50 to 120° C. and drying the varnish; and

[0017] Step 2: After maintaining at 300 to 400° C. for 10 to 120 minutes, maintaining at 420 to 500° C. to carry out imidization.

[0018] The polyamic acid portion has a structural unit derived from tetracarboxylic dianhydride and a structural unit derived from a diamine, and the diamine providing the structural unit derived from the diamine includes a diamine having an ionization potential of 7.10 eV or more.

[0019] [2] The method for producing a polyimide film according to [1] above, wherein the polyimide precursor having a polyamic acid portion is at least one selected from the group consisting of polyamic acid and imide-amic acid copolymers.

[0020] [3] The method for producing a polyimide film according to [1] or [2], wherein the tetracarboxylic dianhydride providing the structural unit derived from tetracarboxylic dianhydride contains tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less.

[0021] [4] The method for producing a polyimide film according to any one of [1] to [3] above, wherein the polyimide precursor contains a repeating unit represented by the following formula (1):

[0022]

[0023] In formula (1), A 1 A is a tetravalent aromatic group having 4 to 39 carbon atoms, 1Optionally having at least one selected from the group consisting of -O-, -SO2-, -CO-, -CH2-, -C(CH3)2-, -C2H4O-, -OCO-, -COO-, -NHCO-, -CONH-, and -S- as a bonding group, B 1 is a group represented by the above general formula (2), X 1 , X 2 are each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms,

[0024] In formula (2), Y 1 , Y 2 Each independently represents a single bond, a group represented by -COO-, or a group represented by -OCO-, and R 1 , R 2 , R 3 Each independently represents an organic group having 1 to 20 carbon atoms, and h, i, j and k are integers of 0 to 4.

[0025] [5] The method for producing a polyimide film according to [4], wherein A 1 is a group represented by the following formula (3),

[0026]

[0027] [6] The method for producing a polyimide film according to any one of [2] to [5], wherein the imide-amic acid copolymer contains a repeating unit represented by the following formula (4):

[0028]

[0029] In formula (4), A 2 is at least one selected from the group consisting of the group represented by the above formula (5) and the group represented by the above formula (6), B 2 is a group represented by the above general formula (2),

[0030] In formula (2), Y 1 , Y 2 Each independently represents a single bond, a group represented by -COO-, or a group represented by -OCO-, and R 1 , R 2 , R 3 Each independently represents an organic group having 1 to 20 carbon atoms, and h, i, j and k are integers of 0 to 4.

[0031] [7] A polyimide film obtained by the production method described in any one of [1] to [6].

[0032] [8] The polyimide film according to [7] above, wherein the weight loss rate at 300 to 400°C measured by heating from 40°C to 550°C at a heating rate of 10°C / min using a differential thermal thermogravimetric measuring apparatus is 0.2% or less.

[0033] [9] The polyimide film according to [7] or [8], wherein the yellowness index of the polyimide film when the thickness is 10 μm is less than 30, and the tensile elongation of the polyimide film when subjected to a tensile test with a test piece size of 10 mm × 70 mm and a distance between clamps of 50 mm is 10% or more.

[0034] Effects of the Invention

[0035] According to the present invention, there is provided a method for producing a polyimide film, which can sufficiently realize the imidization reaction and molecular weight increase of a polyimide precursor, and can obtain a polyimide film having high colorless transparency, high elongation and excellent heat resistance. DETAILED DESCRIPTION

[0036] [Method for producing polyimide film]

[0037] The method for producing a polyimide film of the present invention comprises: step 1, removing the solvent from a varnish containing a polyimide precursor having a polyamic acid portion and a solvent at 50 to 120° C. and drying; and step 2, maintaining at 300 to 400° C. for 10 to 120 minutes and then maintaining at 420 to 500° C. to perform imidization; the polyamic acid portion comprises a structural unit derived from tetracarboxylic dianhydride and a structural unit derived from a diamine, and the diamine providing the structural unit derived from the diamine comprises a diamine having an ionization potential of 7.10 eV or more.

[0038] [Process 1]

[0039] The method for producing a polyimide film of the present invention comprises steps 1 and 2 as described above. Step 1 is a step of removing the solvent from a varnish containing a polyimide precursor having a polyamic acid portion and a solvent at 50 to 120° C. and drying the varnish, wherein the polyamic acid portion has a structural unit derived from tetracarboxylic dianhydride and a structural unit derived from a diamine, and the diamine providing the structural unit derived from the diamine contains a diamine having an ionization potential of 7.10 eV or more.

[0040] <Polyimide precursor having a polyamic acid moiety>

[0041] Regarding the polyimide precursor having a polyamic acid portion contained in the varnish used in step 1, it has a polyamic acid portion, and the polyamic acid portion has a structural unit derived from tetracarboxylic dianhydride and a structural unit derived from diamine. The diamine providing the aforementioned structural unit derived from diamine contains a diamine with an ionization potential of 7.10 eV or more, and it can be a polyimide after imidization in step 2, without any particular limitation.

[0042] The polyimide precursor having a polyamic acid portion is preferably at least one selected from the group consisting of polyamic acid and an imide-amic acid copolymer, and more preferably an imide-amic acid copolymer. An imide-amic acid copolymer is a copolymer having an amic acid portion (polyamic acid portion) and an imide portion (polyimide portion) in one molecule.

[0043] [Polyamic acid]

[0044] The polyamic acid is a polymer having only an amic acid portion (polyamic acid portion) and no imide portion (polyimide portion) as a structure that becomes a polyimide after imidization.

[0045] The polyamic acid portion has a structural unit derived from tetracarboxylic dianhydride and a structural unit derived from a diamine, and the diamine providing the structural unit derived from the diamine includes a diamine having an ionization potential of 7.10 eV or more.

[0046] (Structural unit derived from tetracarboxylic dianhydride (structural unit AA))

[0047] The structural unit derived from tetracarboxylic dianhydride which comprises a polyamic acid part is hereinafter also called "structural unit AA".

[0048] It is preferable that the tetracarboxylic dianhydride which provides the structural unit (structural unit AA) derived from tetracarboxylic dianhydride contains tetracarboxylic dianhydride whose electron affinity is 2.5 eV or less.

[0049] The reason why the obtained polyimide film has low colorless transparency is the ease with which the charge moves within the molecule. The higher the electron affinity (Ea) of the tetracarboxylic dianhydride used as the raw material, the easier the charge moves, and thus the obtained polyimide film has low colorless transparency. Therefore, it can be considered that in order to make the polyimide film have high colorless transparency, the electron affinity (Ea) of the tetracarboxylic dianhydride is preferably low.

[0050] On the other hand, the lower the electron affinity (Ea) of the tetracarboxylic dianhydride used as the raw material, the lower the reactivity. Therefore, when the thermal imidization is not carried out under appropriate drying conditions, sufficient thermal imidization and increase in molecular weight are not carried out, and colorless transparency may be impaired. It can be considered that according to the manufacturing method of the present invention, even if a raw material that is effective for high colorless transparency but has low reactivity as described above is used, sufficient thermal imidization can be carried out, and then the molecular weight can be increased, and the obtained polyimide film will become high colorless transparency, and then also have high elongation and heat resistance.

[0051] The tetracarboxylic dianhydride providing the structural unit derived from tetracarboxylic dianhydride (structural unit AA) preferably contains tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less, more preferably contains tetracarboxylic dianhydride having an electron affinity of 2.4 eV or less, and further preferably contains tetracarboxylic dianhydride having an electron affinity of 2.3 eV or less.

[0052] The Ea of the above-mentioned tetracarboxylic dianhydride is a value calculated by the DFT method using Gaussian 16W, using B3LYP using the unrestricted Hartree-Fock method as the functional, using 6-311++G(d,p) as the basis function constituting the molecular orbital, and using the B3LYP / 6-311G(d) basis set using the restricted Hartree-Fock method as the structural parameters of each tetracarboxylic dianhydride.

[0053] Regarding the electron affinity of the tetracarboxylic dianhydride, in the case of a symmetrical monomer, the electron affinity of the two acid dianhydride groups is the same, so the value of the electron affinity is 1. On the other hand, in the case of an asymmetric monomer, the electron affinity of the two acid dianhydride groups is different, so the value of the electron affinity is 2. In the case of an asymmetric monomer, when the first electron affinity and the second electron affinity are both 2.5 eV or less, it is assumed that "the electron affinity of the tetracarboxylic dianhydride is 2.5 eV or less".

[0054] The structural unit AA preferably contains a structural unit derived from tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less, more preferably contains a structural unit derived from tetracarboxylic dianhydride having an electron affinity of 2.4 eV or less, and further preferably contains a structural unit derived from tetracarboxylic dianhydride having an electron affinity of 2.3 eV or less.

[0055] The compound providing a structural unit derived from tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less is preferably at least one selected from the group consisting of a compound represented by the following formula (a1), a compound represented by the following formula (a2) and a compound represented by the following formula (a3), and more preferably a compound represented by the following formula (a1).

[0056]

[0057] The compound represented by formula (a1) is 3,3′,4,4′-biphenyltetracarboxylic dianhydride (s-BPDA) (Ea: 2.24 eV).

[0058] The compound represented by formula (a2) is 9,9′-bis(3,4-dicarboxyphenyl)fluorene anhydride (BPAF) (Ea: 1.94 eV).

[0059] The compound represented by formula (a3) ​​is spiro[11H-difurano[3,4-b:3′,4′-i]xanthene-11,9′-[9H]fluorene]-1,3,7,9-tetraone (SFDA) (Ea: 2.08 eV).

[0060] By including the structural unit AA in the above structural unit, a polyimide film having high elongation and high colorless transparency can be obtained.

[0061] The structural unit AA may contain a structural unit other than the structural unit derived from the compound represented by the formula (a1) or the structural unit derived from the compound represented by the formula (a2).

[0062] In the structural unit AA, the total ratio of the structural unit derived from the compound represented by formula (a1) and the structural unit derived from the compound represented by formula (a2) is preferably 45 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the ratio is not particularly limited and is 100 mol% or less. The structural unit AA preferably contains at least one of the group consisting of the structural unit derived from the compound represented by formula (a1) and the structural unit derived from the compound represented by formula (a2), and more preferably contains the structural unit derived from the compound represented by formula (a1). In addition, the structural unit AA is more preferably at least one of the group consisting of the structural unit derived from the compound represented by formula (a1) and the structural unit derived from the compound represented by formula (a2), and more preferably the structural unit derived from the compound represented by formula (a1).

[0063] When the structural unit AA contains a structural unit derived from a compound represented by formula (a1) and a structural unit derived from a compound represented by formula (a2), the ratio of each structural unit in the structural unit AA is not particularly limited, and any ratio may be adopted.

[0064] (Structural unit derived from diamine (structural unit AB))

[0065] The structural unit derived from the diamine constituting the polyamic acid part is hereinafter also referred to as "structural unit AB".

[0066] The diamine providing the diamine-derived structural unit (structural unit AB) contains a diamine having an ionization potential of 7.10 eV or more.

[0067] The reason why the obtained polyimide film has low colorless transparency is the ease with which the charge moves within the molecule. The lower the ionization potential (Ip) of the diamine used as the raw material, the easier the charge moves, and thus the obtained polyimide film has low colorless transparency. Therefore, it can be considered that in order to make the polyimide film have high colorless transparency, the ionization potential (Ip) of the diamine is preferably high.

[0068] On the other hand, generally speaking, the higher the ionization potential (Ip) of the diamine used as the raw material, the lower the reactivity. Therefore, when thermal imidization is not carried out under appropriate drying conditions, sufficient thermal imidization and increase in molecular weight are not carried out, which may damage the colorless transparency. It can be considered that according to the manufacturing method of the present invention, even if a raw material that is effective for high colorless transparency but has low reactivity as described above is used, thermal imidization can be fully carried out, and the molecular weight can be increased, so that the polyimide film obtained becomes high colorless transparency, and then also has higher elongation and heat resistance.

[0069] The diamine providing the diamine-derived structural unit (structural unit AB) preferably contains a diamine having an ionization potential (Ip) of 7.10 eV or more, more preferably contains a diamine having an ionization potential (Ip) of 7.20 eV or more, and further preferably contains a diamine having an ionization potential (Ip) of 7.30 eV or more.

[0070] The ionization potential (Ip) of the above-mentioned diamine is a value calculated by the DFT method using Gaussian 16W, using B3LYP using the unrestricted Hartree-Fock method as a functional, 6-311++G(d,p) as a basis function constituting a molecular orbital, and using the B3LYP / 6-311G(d) basis set using the restricted Hartree-Fock method as the structural parameters of each diamine.

[0071] In the case of the ionization potential (Ip) of the diamine described above, when it is a symmetrical monomer, the ionization potential (Ip) of the two amino groups is the same, so the value of the ionization potential is 1. On the other hand, in the case of an asymmetric monomer, the ionization potential (Ip) of the two amino groups is different, so the value of the ionization potential is 2. In the case of an asymmetric monomer, when the first ionization potential and the second ionization potential are both 7.10 eV or more, it is assumed that "the ionization potential (Ip) of the diamine is 7.10 eV or more".

[0072] The structural unit AB preferably contains a structural unit derived from a diamine having an ionization potential (Ip) of 7.10 eV or more, more preferably contains a structural unit derived from a diamine having an ionization potential (Ip) of 7.20 eV or more, and further preferably contains a structural unit derived from a diamine having an ionization potential (Ip) of 7.30 eV or more.

[0073] The compound providing a structural unit derived from a diamine having an ionization potential (Ip) of 7.10 eV or more is preferably at least one selected from the group consisting of a compound represented by the following formula (b1), a compound represented by the following formula (b2), and a compound represented by the following formula (b3), and more preferably a compound represented by the following formula (b1).

[0074]

[0075] The compound represented by formula (b1) is 4-aminophenyl-4-aminobenzoate (4-BAAB) (Ip: 7.59 eV and 7.68 eV).

[0076] The compound represented by formula (b2) is 2,2′-bis(trifluoromethyl)benzidine (TFMB) (Ip: 7.55 eV).

[0077] The compound represented by formula (b3) is 1,4-bis(4-aminobenzoyloxy)benzene (ABHQ) (Ip: 7.64 eV).

[0078] When the structural unit AB contains the above structural unit, a polyimide film having high elongation, high colorless transparency, and excellent heat resistance can be obtained.

[0079] The structural unit AB may contain a structural unit other than the structural unit derived from the compound represented by the formula (b1) or the structural unit derived from the compound represented by the formula (b2).

[0080] In the structural unit AB, the total ratio of the structural unit derived from the compound shown in formula (b1) and the structural unit derived from the compound shown in formula (b2) is preferably 45 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the ratio is not particularly limited and is 100 mol% or less. The structural unit AB preferably contains at least one of the group consisting of the structural unit derived from the compound shown in formula (b1) and the structural unit derived from the compound shown in formula (b2), and more preferably contains the structural unit derived from the compound shown in formula (b1). In addition, the structural unit AB is more preferably at least one of the group consisting of the structural unit derived from the compound shown in formula (b1) and the structural unit derived from the compound shown in formula (b2), and more preferably the structural unit derived from the compound shown in formula (b1).

[0081] When the structural unit AB includes a structural unit derived from the compound represented by formula (b1) and a structural unit derived from the compound represented by formula (b2), the ratio of each structural unit in the structural unit AB is not particularly limited, and any ratio may be adopted.

[0082] (Repeating unit represented by formula (1) (amic acid part))

[0083] The polyimide precursor preferably contains a repeating unit represented by the following formula (1). The repeating unit represented by the following formula (1) is an amic acid moiety (polyamic acid moiety), and therefore the polyimide precursor includes both a polyamic acid and an imide-amic acid copolymer.

[0084]

[0085] (In formula (1), A 1 is a tetravalent aromatic group having 4 to 39 carbon atoms, and optionally has at least one selected from the group consisting of -O-, -SO2-, -CO-, -CH2-, -C(CH3)2-, -C2H4O-, -OCO-, -COO-, -NHCO-, -CONH-, and -S- as a bonding group, B 1 is a group represented by the above general formula (2), X 1 , X 2 Each is independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms.

[0086] In formula (2), Y 1 , Y 2 Each independently represents a single bond, a group represented by -COO-, or a group represented by -OCO-. 1 , R 2 , R 3Each independently represents an organic group having 1 to 20 carbon atoms. h, i, j, and k are integers of 0 to 4.

[0087] In the above formula (1), A 1 It is a tetravalent aromatic group having 4 to 39 carbon atoms, and optionally has at least one selected from the group consisting of -O-, -SO2-, -CO-, -CH2-, -C(CH3)2-, -C2H4O-, -OCO-, -COO-, -NHCO-, -CONH-, and -S- as a bonding group.

[0088] A 1 It is obtained by removing two dicarboxylic anhydride parts (four carboxyl parts) from tetracarboxylic dianhydride. 1 The four carbonyl groups bonded thereto are structural units derived from tetracarboxylic dianhydride.

[0089] Here, the tetravalent aromatic group means that the four carbon atoms bonded to the imide group are all aromatic carbon atoms. 1 When there are two or more aromatic rings, the bonding group that bonds the aromatic rings. It should be noted that the bonding group is not limited to these. 1 An aromatic group is preferred because the heat resistance of the polyimide becomes good.

[0090] A 1 It is a tetravalent aromatic group having 4 to 39 carbon atoms, and among them, a group represented by the following formula (3) is preferred, and a group represented by the following formula (3a) is more preferred.

[0091]

[0092] In the above formula (1), X 1 , X 2 Each is independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms, and is preferably a hydrogen atom.

[0093] In the above formula (1), B 1 It is a group represented by the following general formula (2).

[0094] In formula (2), Y 1 , Y 2 Each independently represents a group represented by -COO- or a group represented by -OCO-. 1 , R 2 , R 3 Each independently represents an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or a trifluoromethyl group, preferably a hydrogen atom. h, i, j, and k are integers of 0 to 4, preferably 0.

[0095] Among the groups represented by the formula (2), the groups represented by the following formula (2a) are preferred.

[0096]

[0097] In formula (2), Y 1 , Y 2 Each independently represents a group represented by -COO- or a group represented by -OCO-. 1 , R 2 , R 3 Each independently represents an organic group having 1 to 20 carbon atoms. h, i, j, and k are integers of 0 to 4.

[0098] (Composition of polyamic acid)

[0099] When the aforementioned polyimide precursor is a polyamic acid, the mass ratio of the amic acid portion to the polyamic acid is preferably 50 mass % or more, more preferably 70 mass % or more, further preferably 80 mass % or more, more preferably 82 mass % or more, preferably 85 mass % or more, more preferably 90 mass % or more, preferably 95 mass % or more, and the upper limit is not limited and is 100 mass % or less.

[0100] When the aforementioned polyimide precursor is polyamic acid, the molar ratio of the amic acid portion to the polyamic acid is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, preferably 82 mol% or more, more preferably 85 mol% or more, preferably 90 mol% or more, preferably 95 mol% or more, and the upper limit is not limited and is 100 mol% or less.

[0101] [Imide-amic acid copolymer]

[0102] The imide-amic acid copolymer has an amic acid portion (polyamic acid portion) and an imide portion (polyimide portion) in one molecule.

[0103] However, the amic acid part (polyamic acid part) is the same as the aforementioned [polyamic acid], and the preferred structure is also the same.

[0104] Therefore, the following description will focus on the imide portion (polyimide portion).

[0105] (Structural unit derived from tetracarboxylic dianhydride (structural unit IA))

[0106] The polyimide part has a structural unit derived from tetracarboxylic dianhydride and a structural unit derived from diamine.

[0107] The structural unit derived from tetracarboxylic dianhydride which comprises a polyimide part is hereinafter also called "structural unit IA".

[0108] It is preferable that the tetracarboxylic dianhydride which provides the structural unit (structural unit IA) derived from tetracarboxylic dianhydride contains tetracarboxylic dianhydride whose electron affinity is 2.5 eV or less.

[0109] The reason why the obtained polyimide film has low colorless transparency is the ease with which the charge moves within the molecule. The higher the electron affinity (Ea) of the tetracarboxylic dianhydride used as the raw material, the easier it is for the charge to move, and thus the obtained polyimide film has low colorless transparency. Therefore, in order to make the polyimide film have high colorless transparency, it is considered that the electron affinity (Ea) of the tetracarboxylic dianhydride is preferably low.

[0110] The tetracarboxylic dianhydride providing the structural unit derived from tetracarboxylic dianhydride (structural unit IA) preferably contains tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less, more preferably contains tetracarboxylic dianhydride having an electron affinity of 2.4 eV or less, and further preferably contains tetracarboxylic dianhydride having an electron affinity of 2.3 eV or less.

[0111] The Ea of the above-mentioned tetracarboxylic dianhydride is a value calculated by the DFT method using Gaussian 16W, using B3LYP using the unrestricted Hartree-Fock method as the functional, using 6-311++G(d,p) as the basis function constituting the molecular orbital, and using the B3LYP / 6-311G(d) basis set using the restricted Hartree-Fock method as the structural parameters of each tetracarboxylic dianhydride.

[0112] Regarding the electron affinity of the tetracarboxylic dianhydride, in the case of a symmetrical monomer, the electron affinity of the two acid dianhydride groups is the same, so the value of the electron affinity is 1. On the other hand, in the case of an asymmetric monomer, the electron affinity of the two acid dianhydride groups is different, so the value of the electron affinity is 2. In the case of an asymmetric monomer, when the first electron affinity and the second electron affinity are both 2.3 eV or less, it is assumed that "the electron affinity of the tetracarboxylic dianhydride is 2.3 eV or less".

[0113] The structural unit IA preferably contains a structural unit derived from tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less, more preferably contains a structural unit derived from tetracarboxylic dianhydride having an electron affinity of 2.4 eV or less, and further preferably contains a structural unit derived from tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less.

[0114] The compound providing a structural unit derived from tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less is preferably at least one selected from the group consisting of a compound represented by the following formula (a1), a compound represented by the following formula (a2), and a compound represented by the following formula (a3), and more preferably a compound represented by the following formula (a2).

[0115]

[0116] The compound represented by formula (a1) is 3,3′,4,4′-biphenyltetracarboxylic dianhydride (s-BPDA) (Ea: 2.24 eV).

[0117] The compound represented by formula (a2) is 9,9′-bis(3,4-dicarboxyphenyl)fluorene anhydride (BPAF) (Ea: 1.94 eV).

[0118] The compound represented by formula (a3) ​​is spiro[11H-difurano[3,4-b:3′,4′-i]xanthene-11,9′-[9H]fluorene]-1,3,7,9-tetraone (SFDA) (Ea: 2.08 eV).

[0119] When the structural unit IA contains the above structural unit, a polyimide film having high elongation, high colorless transparency, and excellent heat resistance can be obtained.

[0120] The structural unit IA may contain a structural unit other than the structural unit derived from the compound represented by the formula (a1) or the structural unit derived from the compound represented by the formula (a2).

[0121] In the structural unit IA, the total ratio of the structural unit derived from the compound shown in formula (a1) and the structural unit derived from the compound shown in formula (a2) is preferably 45 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the ratio is not particularly limited and is 100 mol% or less. The structural unit IA preferably contains at least one of the group consisting of the structural unit derived from the compound shown in formula (a1) and the structural unit derived from the compound shown in formula (a2), and more preferably contains the structural unit derived from the compound shown in formula (a2). In addition, the structural unit IA is more preferably selected from at least one of the group consisting of the structural unit derived from the compound shown in formula (a1) and the structural unit derived from the compound shown in formula (a2), and is further preferably a structural unit derived from the compound shown in formula (a1).

[0122] When the structural unit IA contains a structural unit derived from the compound represented by formula (a1) and a structural unit derived from the compound represented by formula (a2), the ratio of each structural unit in the structural unit IA is not particularly limited, and any ratio may be adopted.

[0123] (Structural unit derived from diamine (structural unit IB))

[0124] The structural unit derived from diamine constituting the polyimide part is hereinafter also referred to as "structural unit IB".

[0125] The diamine providing the diamine-derived structural unit (structural unit IB) preferably contains a diamine having an ionization potential of 7.10 eV or more.

[0126] The reason why the obtained polyimide film has low colorless transparency is the ease of charge movement in the molecule. The lower the ionization potential (Ip) of the diamine used as the raw material, the easier it is for the charge to move, so the obtained polyimide film has low colorless transparency. Therefore, it can be considered that in order to make the polyimide film have high colorless transparency, the ionization potential (Ip) of the diamine is preferably high.

[0127] The diamine providing the diamine-derived structural unit (structural unit IB) preferably contains a diamine having an ionization potential (Ip) of 7.10 eV or more, more preferably contains a diamine having an ionization potential (Ip) of 7.20 eV or more, and further preferably contains a diamine having an ionization potential (Ip) of 7.30 eV or more.

[0128] The ionization potential (Ip) of the above-mentioned diamine is a value calculated by the DFT method using Gaussian 16W, using B3LYP using the unrestricted Hartree-Fock method as a functional, 6-311++G(d,p) as a basis function constituting a molecular orbital, and using the B3LYP / 6-311G(d) basis set using the restricted Hartree-Fock method as the structural parameters of each diamine.

[0129] Regarding the ionization potential (Ip) of the diamine, in the case of a symmetric monomer, the ionization potential (Ip) of the two amino groups is the same, so the value of the ionization potential is 1. On the other hand, in the case of an asymmetric monomer, the ionization potential (Ip) of the two amino groups is different, so the value of the ionization potential is 2. In the case of an asymmetric monomer, when the first ionization potential and the second ionization potential are both 7.10 eV or more, it is assumed that "the ionization potential (Ip) of the diamine is 7.10 eV or more".

[0130] The structural unit IB preferably contains a structural unit derived from a diamine having an ionization potential (Ip) of 7.10 eV or more, more preferably contains a structural unit derived from a diamine having an ionization potential (Ip) of 7.20 eV or more, and further preferably contains a structural unit derived from a diamine having an ionization potential (Ip) of 7.30 eV or more.

[0131] The compound providing a structural unit derived from a diamine having an ionization potential (Ip) of 7.10 eV or more is preferably at least one selected from the group consisting of a compound represented by the following formula (b1), a compound represented by the following formula (b2) and a compound represented by the following formula (b3), and more preferably a compound represented by the following formula (b1).

[0132]

[0133] The compound represented by formula (b1) is 4-aminophenyl-4-aminobenzoate (4-BAAB) (Ip: 7.59 eV and 7.68 eV).

[0134] The compound represented by formula (b2) is 2,2′-bis(trifluoromethyl)benzidine (TFMB) (Ip: 7.55 eV).

[0135] The compound represented by formula (b3) is 1,4-bis(4-aminobenzoyloxy)benzene (ABHQ) (Ip: 7.64 eV).

[0136] When the structural unit IB contains the above structural unit, a polyimide film having high elongation and high colorless transparency can be obtained.

[0137] The structural unit IB may contain a structural unit other than the structural unit derived from the compound represented by the formula (b1) or the structural unit derived from the compound represented by the formula (b2).

[0138] In the structural unit IB, the total ratio of the structural unit derived from the compound shown in formula (b1) and the structural unit derived from the compound shown in formula (b2) is preferably 45 mol% or more, more preferably 70 mol% or more, further preferably 90 mol% or more, and particularly preferably 99 mol% or more. The upper limit of the ratio is not particularly limited and is 100 mol% or less. The structural unit IB preferably contains at least one of the groups consisting of the structural unit derived from the compound shown in formula (b1) and the structural unit derived from the compound shown in formula (b2), and more preferably contains the structural unit derived from the compound shown in formula (b1). In addition, the structural unit IB is more preferably at least one of the groups consisting of the structural unit derived from the compound shown in formula (b1) and the structural unit derived from the compound shown in formula (b2), and more preferably the structural unit derived from the compound shown in formula (b1).

[0139] When the structural unit IB contains a structural unit derived from the compound represented by formula (b1) and a structural unit derived from the compound represented by formula (b2), the ratio of each structural unit in the structural unit IB is not particularly limited, and any ratio may be adopted.

[0140] (Repeating unit represented by formula (4) (imide moiety))

[0141] The imide-amic acid copolymer used as the polyimide precursor preferably contains a repeating unit represented by the following formula (4).

[0142]

[0143] (In formula (4), A 2 is at least one selected from the group consisting of the group represented by the above formula (5) and the group represented by the above formula (6), B 2 It is a group represented by the above general formula (2).

[0144] In formula (2), Y 1 , Y 2 Each independently represents a single bond, a group represented by -COO-, or a group represented by -OCO-. 1 , R 2 , R 3 Each independently represents an organic group having 1 to 20 carbon atoms. h, i, j, and k are integers of 0 to 4.)

[0145] In the above formula (4), A 2 It is at least one selected from the group consisting of the group represented by the above formula (5) and the group represented by the above formula (6), and is preferably the group represented by the above formula (5). 2 and A in formula (1) 1 It can be different or the same, preferably the same as A 1 Different tetravalent aromatic groups having 4 to 39 carbon atoms.

[0146] A 2 A is a substance obtained by removing two dicarboxylic anhydride moieties (four carboxyl moieties) from tetracarboxylic dianhydride. 2 The four carbonyl groups bonded thereto are structural units derived from tetracarboxylic dianhydride.

[0147] By A 2 The group represented by the formula (5) or the group represented by the formula (6) is preferred because the heat resistance of the polyimide becomes good.

[0148] In the above formula (4), B 2 It is a group represented by the following general formula (2).

[0149] In formula (2), Y 1 , Y 2 Each independently represents a group represented by -COO- or a group represented by -OCO-. 1 , R 2 , R 3Each independently represents an organic group having 1 to 20 carbon atoms, preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an aryl group having 6 to 10 carbon atoms, or a trifluoromethyl group, preferably a hydrogen atom. h, i, j, and k are integers of 0 to 4, preferably 0.

[0150] Among the groups represented by formula (2), a group represented by the following formula (2a) is preferred.

[0151]

[0152] (In formula (2), Y 1 , Y 2 Each independently represents a group represented by -COO- or a group represented by -OCO-. 1 , R 2 , R 3 Each independently represents an organic group having 1 to 20 carbon atoms. h, i, j, and k are integers of 0 to 4.

[0153] (Constitution of Imide-Amide Acid Copolymer)

[0154] In the imide-amic acid copolymer, the molar ratio [imide / amic acid] of the imide part (repeating unit represented by formula (4)) to the amic acid part (repeating unit represented by formula (1)) is preferably 10 / 90 to 40 / 60, more preferably 10 / 90 to 30 / 70, and further preferably 15 / 85 to 30 / 70 from the viewpoint of low yellowness, high heat resistance and elongation.

[0155] The mass ratio of the total of the imide part and the amic acid part to the imide-amic acid copolymer is preferably 50 mass% or more, more preferably 70 mass% or more, further preferably 80 mass% or more, preferably 82 mass% or more, more preferably 85 mass% or more, preferably 90 mass% or more, more preferably 95 mass% or more, and the upper limit is not limited and is 100 mass% or less.

[0156] The molar ratio of the total of the imide part and the amic acid part to the imide-amic acid copolymer is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, preferably 82 mol% or more, more preferably 85 mol% or more, preferably 90 mol% or more, more preferably 95 mol% or more, and the upper limit is not limited and is 100 mol% or less.

[0157] [Method for producing polyimide precursor]

[0158] The polyimide precursor can be produced by any method. When the polyimide precursor is an imide-amic acid copolymer, it is preferably obtained by a production method having the following steps a and b.

[0159] Step a: a step of reacting tetracarboxylic dianhydride constituting the imide portion with diamine to obtain an imide oligomer

[0160] Step b: a step of reacting the imide oligomer obtained in step 1 with tetracarboxylic dianhydride and diamine constituting the amic acid portion to obtain an imide-amic acid copolymer

[0161] It can be considered that: according to the present manufacturing method, the imide part and the amic acid part can be controlled to have a specific structure. Therefore, unlike the known imide-amic acid copolymers in which the imide part and the amic acid part exist randomly, based on the thermal imidization reactivity of each component, an imide-amic acid copolymer having a polyimide part and a polyamic acid part and expected to have improved heat resistance can be obtained.

[0162] In addition, when the polyimide precursor is a polyamic acid, it can be manufactured only by the aforementioned step b (without using an imide oligomer). That is, it is preferred to obtain it by a manufacturing method having a step of obtaining an imide-amic acid copolymer, in which the tetracarboxylic dianhydride constituting the amic acid portion is reacted with a diamine in the step of obtaining the imide-amic acid copolymer. The preferred conditions are the same as those in step b.

[0163] Step a is a step of reacting tetracarboxylic dianhydride constituting the imide portion with diamine to obtain an imide oligomer.

[0164] In step a, the molar ratio of diamine to tetracarboxylic dianhydride (diamine / tetracarboxylic dianhydride) is preferably 1.01 to 2 mol, more preferably 1.05 to 1.9 mol, and further preferably 1.1 to 1.7 mol.

[0165] The method for reacting tetracarboxylic dianhydride and diamine in order to obtain an imide oligomer in step a is not particularly limited, and a known method can be adopted.

[0166] Specific reaction methods include: (1) a method in which tetracarboxylic dianhydride, a diamine, and a reaction solvent are placed in a reactor, stirred at 10 to 110° C. for 0.5 to 30 hours, and then the temperature is increased to carry out an imidization reaction; (2) a method in which a diamine and a reaction solvent are placed in a reactor, dissolved, and then tetracarboxylic dianhydride is placed in the reactor, stirred at 10 to 110° C. for 0.5 to 30 hours as required, and then the temperature is increased to carry out an imidization reaction; (3) a method in which tetracarboxylic dianhydride, a diamine, and a reaction solvent are placed in a reactor, and then the temperature is increased to carry out an imidization reaction, etc.

[0167] In the imidization reaction, it is preferred to use a Dean-Stark apparatus or the like to carry out the reaction while removing water generated during the production. By carrying out such an operation, the degree of polymerization and the imidization ratio can be further increased.

[0168] A known imidization catalyst can be used for the above-mentioned imidization reaction. Examples of the imidization catalyst include a base catalyst and an acid catalyst.

[0169] Examples of the base catalyst include organic base catalysts such as pyridine, quinoline, isoquinoline, α-methylpyridine, β-methylpyridine, 2,4-lutidine, 2,6-lutidine, trimethylamine, triethylamine, tripropylamine, tributylamine, triethylenediamine, imidazole, N,N-dimethylaniline, and N,N-diethylaniline; and inorganic base catalysts such as potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium hydrogen carbonate, and sodium hydrogen carbonate.

[0170] Examples of the acid catalyst include crotonic acid, acrylic acid, trans-3-hexenoic acid, cinnamic acid, benzoic acid, methylbenzoic acid, hydroxybenzoic acid, terephthalic acid, benzenesulfonic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid. The imidization catalysts described above may be used alone or in combination of two or more.

[0171] Among the above, from the viewpoint of operability, a base catalyst is preferred, an organic base catalyst is more preferred, at least one selected from triethylamine and triethylenediamine is further preferred, and triethylamine is further preferred.

[0172] From the viewpoint of reaction rate and suppression of gelation, the temperature of the imidization reaction is preferably 120 to 250° C., more preferably 160 to 200° C. The reaction time after the start of distillation of generated water is preferably 0.5 to 10 hours.

[0173] Furthermore, the imide oligomer obtained in step a preferably has amino groups at both ends of the main chain of the molecular chain.

[0174] The above method can obtain a solution containing an imide oligomer dissolved in a solvent. The solution containing an imide oligomer obtained in step a may contain at least a part of the components used as tetracarboxylic dianhydride and diamine in step a as unreacted monomers within a range not impairing the effects of the present invention.

[0175] From the viewpoint of heat resistance and mechanical strength of the obtained polyimide film, the number average molecular weight (Mn) of the imide oligomer obtained in step a is preferably 1,000 to 100,000. In addition, considering the same point of view, the weight average molecular weight (Mw) is preferably 1,000 to 100,000. It should be noted that the number average molecular weight or weight average molecular weight of the copolymer can be obtained, for example, by the standard polymethyl methacrylate (PMMA) conversion value obtained by gel filtration chromatography or by light scattering method.

[0176] Step b is a step of reacting the imide oligomer obtained in step a with tetracarboxylic dianhydride and diamine constituting the amic acid portion to obtain an imide-amic acid copolymer containing repeating units consisting of an imide portion and an amic acid portion.

[0177] The method for reacting tetracarboxylic dianhydride with the imide oligomer obtained in step a to obtain an imide-amic acid copolymer in step b is not particularly limited, and a known method can be adopted.

[0178] Specific reaction methods include: (1) a method in which the imide oligomer obtained in step a, tetracarboxylic dianhydride, diamine and solvent are introduced into a reactor and stirred at a temperature in the range of 0 to 120° C., preferably 5 to 80° C., for 1 to 72 hours; (2) a method in which the imide oligomer obtained in step a and a solvent are introduced into a reactor and dissolved, and then tetracarboxylic dianhydride and diamine are introduced and stirred at a temperature in the range of 0 to 120° C., preferably 5 to 80° C., for 1 to 72 hours.

[0179] When the reaction is carried out at 80° C. or lower, the molecular weight of the copolymer obtained in step b does not vary depending on the temperature history during polymerization, and the progress of thermal imidization can be suppressed, so that the copolymer can be produced stably.

[0180] The above method can obtain a copolymer solution containing an imide-amic acid copolymer dissolved in a solvent. In addition, the above method without using an imide oligomer can obtain a copolymer solution containing a polyamic acid dissolved in a solvent.

[0181] The concentration of the polyimide precursor in the obtained polyimide precursor solution is preferably 1 to 50% by mass, more preferably 3 to 35% by mass, and further preferably 5 to 30% by mass.

[0182] The concentration of the copolymer in the obtained copolymer solution is preferably 1 to 50% by mass, more preferably 3 to 35% by mass, and even more preferably 5 to 30% by mass.

[0183] The concentration of the polyamic acid in the obtained polyamic acid solution is preferably 1 to 50% by mass, more preferably 3 to 35% by mass, and further preferably 5 to 30% by mass.

[0184] From the viewpoint of the mechanical strength of the obtained polyimide film, the number average molecular weight of the polyimide precursor is preferably 5,000 to 500,000. In addition, from the same viewpoint, the weight average molecular weight (Mw) of the polyimide precursor is preferably 10,000 to 800,000, more preferably 10,000 to 300,000, and further preferably 100,000 to 300,000. It should be noted that the number average molecular weight of the polyimide precursor can be obtained, for example, by the standard polymethyl methacrylate (PMMA) conversion value obtained by gel filtration chromatography.

[0185] As the tetracarboxylic dianhydride and diamine as raw materials used in the method for producing the polyimide precursor, it is preferable to use compounds which provide the structural units described in the structural unit section of the polyimide precursor, and the preferred ranges are the same.

[0186] It should be noted that the tetracarboxylic dianhydride may include acid dianhydride, but is not limited thereto, and may also be a derivative thereof within the scope of providing the same structural unit. As the derivative, tetracarboxylic acid and the alkyl ester of the tetracarboxylic acid may be listed, among which acid dianhydride is preferred. As the diamine, diamine may be listed, but is not limited thereto, and may also be a derivative thereof within the scope of providing the same structural unit. As the derivative, diisocyanate corresponding to diamine may be listed, among which diamine is preferred.

[0187] A terminal blocking agent may be used in the production of the polyimide precursor. The terminal blocking agent is preferably used in step b.

[0188] The end-capping agent is preferably a monoamine or a dicarboxylic acid. The feed amount of the end-capping agent introduced is preferably 0.0001 to 0.1 mole, and more preferably 0.001 to 0.06 mole, relative to 1 mole of tetracarboxylic dianhydride. As a monoamine end-capping agent, for example, methylamine, ethylamine, propylamine, butylamine, benzylamine, 4-methylbenzylamine, 4-ethylbenzylamine, 4-dodecylbenzylamine, 3-methylbenzylamine, 3-ethylbenzylamine, aniline, 3-methylaniline, 4-methylaniline, etc. Among these, benzylamine and aniline are preferred. As a dicarboxylic acid end-capping agent, a dicarboxylic acid is preferably used, a part of which can be ring-closed. For example, phthalic acid, phthalic anhydride, 4-chlorophthalic acid, tetrafluorophthalic acid, 2,3-benzophenone dicarboxylic acid, 3,4-benzophenone dicarboxylic acid, cyclopentane-1,2-dicarboxylic acid, 4-cyclohexene-1,2-dicarboxylic acid, etc. can be listed. Among these, phthalic acid and phthalic anhydride are preferred.

[0189] A solvent may also be used as a reaction solvent. Any solvent may be used as long as it can dissolve the generated polyimide precursor. Examples thereof include aprotic solvents, phenolic solvents, ether solvents, carbonate solvents, etc., and preferred solvents are the same as those used in the varnish described below.

[0190] <Varnish and solvent>

[0191] The varnish used in step 1 contains the above-mentioned polyimide precursor and a solvent.

[0192] The solvent may be any solvent that can dissolve the polyimide precursor, and examples thereof include aprotic solvents, phenolic solvents, etheric solvents, and carbonate-based solvents.

[0193] Specific examples of aprotic solvents include amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-methylcaprolactam, 1,3-dimethylimidazolidinone, and tetramethylurea; lactone solvents such as γ-butyrolactone and γ-valerolactone; phosphorus-containing amide solvents such as hexamethylphosphoric acid amide and hexamethylphosphine triamide; sulfur-containing solvents such as dimethyl sulfone, dimethyl sulfoxide, and cyclopentane; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methylcyclohexanone; and ester solvents such as acetic acid (2-methoxy-1-methylethyl ester).

[0194] Specific examples of the phenolic solvent include phenol, o-cresol, m-cresol, p-cresol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, and 3,5-xylenol.

[0195] Specific examples of the ether solvent include 1,2-dimethoxyethane, bis(2-methoxyethyl)ether, 1,2-bis(2-methoxyethoxy)ethane, bis[2-(2-methoxyethoxy)ethyl]ether, tetrahydrofuran, and 1,4-dioxane.

[0196] Specific examples of the carbonate-based solvent include diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, and propylene carbonate.

[0197] Among the above solvents, amide solvents or lactone solvents are preferred, amide solvents are more preferred, and N-methyl-2-pyrrolidone is further preferred. The above solvents may be used alone or in combination of two or more.

[0198] The varnish may be the polyimide precursor solution itself, or may be a product obtained by adding a diluting solvent to the polyimide precursor solution.

[0199] The varnish may be the above-mentioned copolymer solution itself, or may be a varnish obtained by further adding a diluting solvent to the copolymer solution.

[0200] The varnish may be the polyamic acid solution itself or a product obtained by further adding a diluting solvent to the polyamic acid solution.

[0201] From the viewpoint of efficiently carrying out the imidization of the amic acid portion of the polyimide precursor, the varnish of the present invention may further contain an imidization catalyst and a dehydration catalyst. The imidization catalyst may be an imidization catalyst having a boiling point of 40° C. or higher. If the imidization catalyst has a boiling point of 40° C. or higher, the possibility of volatilization before imidization can be fully avoided.

[0202] Examples of the imidization catalyst include amine compounds such as pyridine and picoline, and imidazole compounds such as imidazole, 1,2-dimethylimidazole, 1-benzylimidazole, 1-benzyl-2-methylimidazole, and benzimidazole. The imidization catalysts may be used alone or in combination of two or more.

[0203] Examples of the dehydration catalyst include acid anhydrides such as acetic anhydride, propionic anhydride, n-butyric anhydride, benzoic anhydride, and trifluoroacetic anhydride; and carbodiimide compounds such as dicyclohexylcarbodiimide. These may be used alone or in combination of two or more.

[0204] However, most imidization catalysts may deteriorate the storage stability in the varnish state, and remain in the polyimide film after drying, which may cause undesirable conditions such as reduced heat resistance, film floating, and yellowing. Therefore, in terms of stable production of polyimide films, it is preferably not added.

[0205] The varnish preferably contains 3 to 40 mass %, more preferably 5 to 40 mass %, and further preferably 6 to 30 mass % of the polyimide precursor. The viscosity of the varnish is preferably 0.1 to 100 Pa·s, more preferably 0.1 to 20 Pa·s. The viscosity of the varnish is a value measured at 25° C. using an E-type viscometer.

[0206] In addition, the varnish may contain various additives such as inorganic fillers, adhesion promoters, release agents, flame retardants, ultraviolet stabilizers, surfactants, leveling agents, defoaming agents, fluorescent brighteners, crosslinking agents, polymerization initiators, and photosensitizers within the range that does not impair the required properties of the polyimide film.

[0207] The method for producing the varnish is not particularly limited, and a known method can be employed.

[0208] <Drying>

[0209] Step 1 is a step of removing the solvent from a varnish containing a polyimide precursor having a polyamic acid part and a solvent at 50 to 120° C. and drying the varnish.

[0210] In step 1, when the solvent is removed from the varnish and dried, the polyimide varnish is coated on the substrate. The coating method can be a known method. For example, slit coating or spin coating can be used. As the substrate, a smooth plate-like object can be listed, for example, a glass plate, a metal plate, a plastic plate, etc. can be listed.

[0211] “Applying the varnish to the substrate” means that the varnish is poured onto the substrate and formed into a film.

[0212] In step 1, the temperature during drying is 50 to 120°C, preferably 60 to 120°C, more preferably 70 to 120°C, and further preferably 80 to 120°C.

[0213] In step 1, the drying time is preferably 10 to 60 minutes, more preferably 10 to 50 minutes, and even more preferably 10 to 40 minutes.

[0214] During drying, the temperature range maintained may vary, but the range of variation is preferably narrow. The temperature variation during drying is preferably 30°C or less, more preferably 20°C or less, further preferably 10°C or less, and further preferably 5°C or less. A range in which there is substantially no variation is further preferred.

[0215] In step 1, the polyimide film can be formed into a target shape by drying it on the substrate.

[0216] [Process 2]

[0217] The method for producing a polyimide film of the present invention comprises step 1 and step 2. Step 2 is a step of imidizing the film by maintaining the film at 300 to 400° C. for 10 to 120 minutes and then maintaining the film at 420 to 500° C.

[0218] In step 2, the polyimide precursor obtained in step 1 and formed into a film shape is used.

[0219] In step 2, it is believed that by maintaining the polyimide precursor at the above two-stage temperature, the imidization reaction and high molecular weight of the polyimide precursor can be fully achieved, and a polyimide film having high colorless transparency and high elongation and excellent heat resistance can be obtained. Although the reason is not clear, it is believed to be as follows.

[0220] It is believed that if the polyimide precursor is heated sharply without sufficient thermal imidization and molecular weight increase, thermal degradation will occur, and the molecular weight will no longer increase, or it will change to a structure that causes coloration. On the other hand, as in step 2 of the manufacturing method of the present invention, it is believed that by maintaining the polyimide precursor at two stages of temperature, imidization reaction and high molecular weight can be achieved before thermal degradation, and the obtained polyimide film has high colorless transparency and high elongation, and further has excellent heat resistance.

[0221] In step 2, from the viewpoint of promoting the imidization reaction, the polyimide precursor is maintained at two stages of temperature, namely, at least 300 to 400° C. for 10 to 120 minutes and then at 420 to 500° C.

[0222] In step 2, a preheating step may be provided before maintaining the temperature at the two stages described above, and preferably, a preheating step is provided.

[0223] The preheating step is preferably maintained at a temperature of one or more stages, more preferably maintained at a temperature of two or more stages. In addition, it is preferably maintained at a temperature of three or less stages. The preheating step is more preferably maintained at a temperature of two stages.

[0224] By providing the preheating step, it is possible to further suppress the decrease in colorless transparency and elongation.

[0225] When the preheating step is a step of maintaining the temperature in two stages, the temperature in the first stage is preferably 100 to 180° C., more preferably 120 to 150° C. The holding time in the first stage is preferably 10 to 120 minutes, more preferably 20 to 60 minutes. The temperature in the second stage is 180 to 300° C., more preferably 200 to 250° C. The holding time in the second stage is preferably 10 to 120 minutes, more preferably 20 to 60 minutes.

[0226] In the preheating step, the temperature range maintained may vary, but the range of variation is preferably narrow. The temperature variation during drying is preferably 30°C or less, more preferably 20°C or less, further preferably 10°C or less, and further preferably 5°C or less. It is further preferred that the temperature does not vary substantially.

[0227] The method of increasing the temperature during drying in process 1 to the holding temperature of the preheating process in process 2 is not particularly limited. From the viewpoint of not impairing the effects of the present invention and shortening the time required for the manufacture of the polyimide film, the heating rate from the temperature during drying in process 1 to the holding temperature of the preheating process in process 2 is preferably 1 to 10°C / min, more preferably 2 to 9°C / min, and further preferably 3 to 8°C / min.

[0228] The atmosphere of the preheating step may include air, nitrogen, oxygen, hydrogen, nitrogen / hydrogen mixed gas, etc. In order to suppress the coloring of the obtained polyimide film, nitrogen with an oxygen concentration of less than 100 ppm and nitrogen / hydrogen mixed gas containing hydrogen with a hydrogen concentration of less than 0.5% are preferred.

[0229] In step 2, the polyimide precursor is maintained at two stages of temperature, namely, maintaining at least 300 to 400° C. for 10 to 120 minutes and then maintaining at 420 to 500° C.

[0230] The temperature of the first stage is 300 to 400° C., preferably 340 to 390° C. The holding time of the first stage is 10 to 120 minutes, preferably 15 to 60 minutes. It is believed that by maintaining at 300 to 400° C., thermal degradation will not occur, imidization reaction and high molecular weight can be achieved, and the obtained polyimide film becomes highly colorless and transparent, has high elongation, and is also excellent in heat resistance.

[0231] The temperature of the second stage is 420 to 500° C., more preferably 430 to 470° C. The holding time of the second stage is not limited, and the holding time may be 10 to 120 minutes, more preferably 10 to 60 minutes, until the imidization is completed. By holding at 420 to 500° C., the imidization reaction and the high molecular weight can be completed, and a high elongation can be given to the obtained polyimide film.

[0232] In step 2, the temperature range maintained may vary, but the range of variation is preferably narrow. The temperature variation during drying is preferably 30°C or less, more preferably 20°C or less, further preferably 10°C or less, and further preferably 5°C or less. A range in which there is substantially no variation is further preferred.

[0233] The method for increasing the temperature from the holding temperature of the preheating step to the holding temperature of the first stage of step 2 is not particularly limited. From the viewpoint of not impairing the effect of the present invention and shortening the time required for the manufacture of the polyimide film, the heating rate from the holding temperature of the preheating step to the holding temperature of the first stage of step 2 is preferably 1 to 10°C / min, more preferably 2 to 9°C / min, and further preferably 3 to 8°C / min.

[0234] When process 2 does not include a preheating process, the method for increasing the temperature from the drying temperature of process 1 to the holding temperature of the first stage of process 2 is not particularly limited. From the viewpoint of not impairing the effect of the present invention and shortening the time required for the manufacture of the polyimide film, the heating rate from the drying temperature of process 1 to the holding temperature of the first stage of process 2 is preferably 1 to 10°C / min, more preferably 2 to 9°C / min, and further preferably 3 to 8°C / min.

[0235] The atmosphere in step 2 may include air, nitrogen, oxygen, hydrogen, nitrogen / hydrogen mixed gas, etc. In order to suppress the coloring of the obtained polyimide film, nitrogen with an oxygen concentration of less than 100 ppm and nitrogen / hydrogen mixed gas containing hydrogen with a hydrogen concentration of less than 0.5% are preferred.

[0236] [Polyimide film]

[0237] The polyimide film of the present invention is a polyimide film obtained by the above-mentioned production method.

[0238] The thickness of the polyimide film of the present invention can be appropriately selected depending on the intended use, and is preferably 1 to 250 μm, more preferably 5 to 100 μm, and even more preferably 5 to 50 μm.

[0239] The thickness of the polyimide film can be easily controlled by adjusting the solid content concentration and viscosity of the varnish.

[0240] The polyimide film of the present invention has high colorless transparency and high elongation as described above. The preferred physical property values ​​of the polyimide film of the present invention are as follows.

[0241] The yellowness index of the polyimide film when the thickness is 10 μm is preferably 30 or less, more preferably less than 30, further preferably 28 or less, and further preferably 25 or less.

[0242] The tensile elongation of a 10 μm thick polyimide film in a tensile test with a test piece size of 10 mm×70 mm and a distance between clamps of 50 mm is preferably 10% or more, more preferably 11% or more, and even more preferably 12% or more.

[0243] The weight loss rate at 300 to 400°C measured by heating from 40°C to 550°C at a heating rate of 10°C / min using a differential thermal thermogravimetric measuring apparatus is preferably 0.3% or less, more preferably 0.2% or less, and even more preferably 0.1% or less.

[0244] It should be noted that the above-mentioned physical property values ​​of the present invention can be specifically measured by the methods described in Examples.

[0245] The polyimide film of the present invention is preferably used as a film for various members such as color filters, flexible displays, semiconductor components, optical members, etc. The polyimide film of the present invention is particularly preferably used as a substrate for image display devices such as liquid crystal displays and OLED displays.

[0246] In addition, the polyimide film obtained by the production method of the present invention is preferably used as a film for various components such as color filters, flexible displays, semiconductor components, optical components, etc. The polyimide film obtained by the production method of the present invention is particularly preferably used as a substrate for image display devices such as liquid crystal displays and OLED displays.

[0247] Example

[0248] The present invention is specifically described below using examples, but the present invention is not limited by these examples.

[0249] <Thin film properties and evaluation>

[0250] The physical properties and evaluations of the polyimide films obtained in Examples and Comparative Examples were measured and evaluated by the following methods.

[0251] (1) Film thickness

[0252] The film thickness was measured using a micrometer manufactured by MITUTOYO CORPORATION.

[0253] (2) Yellowness Index (YI)

[0254] YI is measured in accordance with JIS K7136:2000 and YI ASTM E313-05 (illuminant D, 65°) using a color turbidity simultaneous measuring device "COH7700" manufactured by Nippon Denshoku Industries Co., Ltd. The smaller the YI value, the better the colorless transparency.

[0255] (3) Weight reduction rate (300-400°C)

[0256] The weight reduction rate from 300°C to 400°C was measured using a differential thermal and thermogravimetric simultaneous measurement device "TG / DTA 6200" of Hitachi High-Tech Science Co., Ltd. The sample (polyimide film) was heated from 40°C to 550°C at a heating rate of 10°C / min in a nitrogen atmosphere, the sample weight at 300°C was set as A, the sample weight at 400°C was set as B, and the value obtained by (AB) / A×100 was set as the weight reduction rate from 300°C to 400°C (300-400°C). The smaller the weight reduction rate, the better the heat resistance.

[0257] (4) Tensile elongation

[0258] The tensile elongation was measured in accordance with JIS K7127: 1999 using a tensile testing machine "STROGRAPH VG-1E" manufactured by Toyo Seiki Co., Ltd. The distance between the grips was 50 mm, the test piece size was 10 mm×70 mm, and the test speed was 20 mm / min.

[0259] The tetracarboxylic dianhydride and diamine used in Examples and Comparative Examples, and their abbreviations and the like are as follows.

[0260] <Tetracarboxylic dianhydride>

[0261] s-BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride (compound represented by formula (a1), Ea: 2.24eV, manufactured by Mitsubishi Chemical Corporation)

[0262] BPAF: 9,9-bis(3,4-dicarboxyphenyl)fluorene anhydride (compound represented by formula (a2), Ea: 1.94 eV, manufactured by JFE Chemical Co., Ltd.)

[0263] SFDA: Spiro[11H-difuran[3,4-b:3',4'-i]xanthene-11,9'-[9H]fluorene]-1,3,7,9-tetraone (compound represented by formula (a3), Ea: 2.08 eV, manufactured by Air Water Performance Chemical Co., Ltd.)

[0264] <Diamine>

[0265] 4-BAAB: 4-aminophenyl-4-aminobenzoate (compound represented by formula (b1), Ip: 7.59 eV and 7.68 eV, manufactured by Japan Junryo Pharmaceutical Co., Ltd.)

[0266] TFMB: 2,2'-bis(trifluoromethyl)benzidine (compound represented by formula (b2), Ip: 7.55 eV, manufactured by SEIKA Corporation)

[0267] ABHQ: 1,4-bis(4-aminobenzoyloxy)benzene (compound represented by formula (b3), Ip: 7.64 eV, manufactured by Mikuni Pharmaceutical Industries, Ltd.)

[0268] PPD: p-phenylenediamine (Ip: 7.04 eV, manufactured by Tokyo Chemical Industry Co., Ltd.)

[0269] The abbreviations of the solvents and catalysts used in Examples and Comparative Examples are as follows.

[0270] NMP: N-methyl-2-pyrrolidone (manufactured by Tokyo Junyaku Industries Co., Ltd.)

[0271] TEA: triethylamine (manufactured by Kanto Chemical Co., Ltd.)

[0272] <Manufacturing of polyimide film>

[0273] Example 1

[0274] In a 500 mL 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet tube, a Dean-Stark apparatus equipped with a condenser, a thermometer, and a glass end cap, 32.765 g (0.144 mol) of 4-BAAB and 180.000 g of NMP were placed, and the temperature in the system was set to 50° C. under a nitrogen atmosphere, and stirred to obtain a solution.

[0275] To this solution, 42.235 g (0.144 mol) of s-BPDA and 120.000 g of NMP were added all at once, and the mixture was stirred at 50° C. for 5 hours. Then, NMP was added to make the solid content concentration uniform so as to be about 15% by mass, thereby obtaining a varnish containing a polyamic acid.

[0276] Then, the obtained varnish was applied to a glass plate by spin coating and kept on a hot plate at 80°C for 20 minutes (step 1). Thereafter, it was kept at 350°C for 15 minutes and at 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0277] Example 2

[0278] In a 500 mL 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet tube, a Dean-Stark apparatus equipped with a condenser, a thermometer, and a glass end cap, 9.370 g (0.041 mol) of 4-BAAB and 207.059 g of NMP were added, and the temperature in the system was set to 70° C. under a nitrogen atmosphere, and stirred to obtain a solution.

[0279] After adding 12.546 g (0.027 mol) of BPAF and 40.000 g of NMP to the solution at once, 0.138 g of TEA and 5.000 g of NMP as an imidization catalyst were added, and the temperature in the reaction system was raised to 180° C. in about 20 minutes by heating with a heating mantle. The temperature in the reaction system was kept at 180° C. and refluxed for 2 hours while collecting the distilled components. Thereafter, the temperature in the reaction system was cooled to 50° C. to obtain a solution containing an oligomer having an imide repeating structural unit.

[0280] 32.250 g (0.110 mol) of s-BPDA, 21.863 g (0.096 mol) of 4-BAAB, and 47.940 g of NMP were added to the obtained solution at once, and the mixture was stirred at 80° C. for 3 hours. NMP was then added to make the solid content concentration about 15% by mass and homogenized to obtain a varnish containing a copolymer having an imide repeating structural unit and an amic acid repeating structural unit (imide-amic acid copolymer).

[0281] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0282] Example 3

[0283] In a 500 mL 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet tube, a Dean-Stark apparatus equipped with a condenser, a thermometer, and a glass end cap, 12.516 g (0.039 mol) of TFMB and 97.348 g of NMP were added, and the temperature in the system was set to 70° C. under a nitrogen atmosphere, and stirred to obtain a solution.

[0284] After adding 11.944 g (0.026 mol) of BPAF and 30.000 g of NMP to the solution at once, 0.132 g of TEA and 5.000 g of NMP as an imidization catalyst were added, and the temperature in the reaction system was raised to 190° C. in about 20 minutes by heating with a heating mantle. The temperature in the reaction system was kept at 190° C. while collecting the distilled components, and refluxed for 1 hour. Thereafter, 128.591 g of NMP was added, and the temperature in the reaction system was cooled to 50° C. to obtain a solution containing an oligomer having an imide repeating structural unit.

[0285] 30.664 g (0.104 mol) of s-BPDA, 20.815 g (0.091 mol) of 4-BAAB, and 40.000 g of NMP were added to the obtained solution at once, and the mixture was stirred at 70° C. for 5 hours. NMP was then added to make the solid content concentration about 15% by mass and homogenized to obtain a varnish containing a copolymer having an imide repeating structural unit and an amic acid repeating structural unit (imide-amic acid copolymer).

[0286] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0287] Example 4

[0288] A varnish was obtained in the same manner as in Example 2.

[0289] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, in a nitrogen atmosphere, the varnish was kept at 120°C for 30 minutes, 200°C for 15 minutes (pre-heating step of step 2), 350°C for 15 minutes, and 450°C for 10 minutes in a hot air dryer to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0290] Example 5

[0291] A varnish was obtained in the same manner as in Example 2.

[0292] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, in a nitrogen atmosphere, the varnish was kept at 150°C for 30 minutes, 200°C for 15 minutes (pre-heating step of step 2), 350°C for 15 minutes, and 450°C for 10 minutes in a hot air dryer to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0293] Example 6

[0294] A varnish was obtained in the same manner as in Example 2.

[0295] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 120°C for 20 minutes on a hot plate (step 1). Thereafter, in a nitrogen atmosphere, the varnish was kept at 150°C for 30 minutes, 200°C for 15 minutes (pre-heating step of step 2), 350°C for 15 minutes, and 450°C for 10 minutes in a hot air dryer to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0296] Example 7

[0297] In a 500 mL 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet tube, a Dean-Stark apparatus equipped with a condenser, a thermometer, and a glass end cap, 9.322 g (0.041 mol) of 4-BAAB and 220.131 g of NMP were added, and the temperature in the system was set to 70° C. under a nitrogen atmosphere, and stirred to obtain a solution.

[0298] After adding SFDA 12.863g (0.027 mol) and NMP 30.000g at once to the solution, 0.138g of TEA and 5.000g of NMP as an imidization catalyst were added, and the temperature in the reaction system was raised to 190°C in about 20 minutes by heating with a heating jacket. The temperature in the reaction system was maintained at 190°C while collecting the distilled components, and refluxed for 1 hour. After that, 29.861g of NMP was added, and the temperature in the reaction system was cooled to 50°C to obtain a solution containing an oligomer having an imide repeating structural unit.

[0299] 32.044 g (0.109 mol) of s-BPDA, 21.752 g (0.095 mol) of 4-BAAB, and 15.000 g of NMP were added to the obtained solution at once, and the mixture was stirred at 70° C. for 5 hours. NMP was then added to make the solid content concentration about 15% by mass and homogenized to obtain a varnish containing a copolymer having an imide repeating structural unit and an amic acid repeating structural unit (imide-amic acid copolymer).

[0300] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, in a nitrogen atmosphere, the varnish was kept at 150°C for 30 minutes, 200°C for 15 minutes (pre-heating step of step 2), 350°C for 15 minutes, and 450°C for 10 minutes in a hot air dryer to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0301] Example 8

[0302] In a 500 mL 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet tube, a Dean-Stark apparatus equipped with a condenser, a thermometer, and a glass end cap, ABHQ11.731 g (0.034 mol) and NMP218.217 g were added, and the temperature in the system was set to 70° C. under a nitrogen atmosphere, and stirred to obtain a solution.

[0303] After adding 10.290 g (0.022 mol) of BPAF and 30.000 g of NMP to the solution at once, 0.114 g of TEA and 5.000 g of NMP as an imidization catalyst were added, and the temperature in the reaction system was raised to 190° C. in about 20 minutes by heating with a heating mantle. The temperature in the reaction system was maintained at 190° C. while collecting the distilled components, and refluxed for 1 hour. Thereafter, 31.778 g of NMP was added, and the temperature in the reaction system was cooled to 50° C. to obtain a solution containing an oligomer having an imide repeating structural unit.

[0304] 26.417 g (0.090 mol) of s-BPDA, 27.371 g (0.079 mol) of ABHQ, and 15.000 g of NMP were added to the obtained solution at once, and the mixture was stirred at 70° C. for 5 hours. NMP was then added to make the solid content concentration about 15% by mass and homogenized to obtain a varnish containing a copolymer having an imide repeating structural unit and an amic acid repeating structural unit (imide-amic acid copolymer).

[0305] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, in a nitrogen atmosphere, the varnish was kept at 150°C for 30 minutes, 200°C for 15 minutes (pre-heating step of step 2), 350°C for 15 minutes, and 450°C for 10 minutes in a hot air dryer to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0306] Example 9

[0307] In a 500 mL 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet tube, a Dean-Stark apparatus equipped with a condenser, a thermometer, and a glass end cap, 31.074 g (0.136 mol) of 4-BAAB and 243.140 g of NMP were added, and the temperature in the system was set to 50° C. under a nitrogen atmosphere, and the mixture was stirred at a rotation speed of 200 rpm to obtain a solution.

[0308] To this solution, 32.044 g (0.109 mol) of s-BPDA, 12.863 g (0.027 mol) of SFDA, and 60.785 g of NMP were added all at once, and stirred at 50° C. for 5 hours. NMP was then added to make the solid content concentration about 15% by mass and homogenized to obtain a varnish containing polyamic acid.

[0309] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0310] Example 10

[0311] In a 500 mL 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet tube, a Dean-Stark apparatus equipped with a condenser, a thermometer, and a glass end cap, 31.233 g (0.137 mol) of 4-BAAB and 243.156 g of NMP were added, and the temperature in the system was set to 50° C. under a nitrogen atmosphere, and the mixture was stirred at a rotation speed of 200 rpm to obtain a solution.

[0312] 32.208 g (0.110 mol) of s-BPDA, 12.546 g (0.027 mol) of SFDA, and 60.789 g of NMP were added to the solution at once, and stirred at 50° C. for 5 hours. NMP was then added to make the solid content concentration about 15% by mass and homogenized to obtain a varnish containing polyamic acid.

[0313] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 1.

[0314] Comparative Example 1

[0315] According to the same method as in Example 1, a varnish was obtained.

[0316] The obtained varnish was then applied to a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film. The properties and evaluation results of the film are shown in Table 2.

[0317] Comparative Example 2

[0318] A varnish was obtained in the same manner as in Example 2.

[0319] The obtained varnish was then applied to a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film. The properties and evaluation results of the film are shown in Table 2.

[0320] Comparative Example 3

[0321] A varnish was obtained in the same manner as in Example 2.

[0322] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 250°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film. The physical properties and evaluation results of the film are shown in Table 2.

[0323] Comparative Example 4

[0324] A varnish was obtained in the same manner as in Example 3.

[0325] The obtained varnish was then applied to a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film. The properties and evaluation results of the film are shown in Table 2.

[0326] Comparative Example 5

[0327] In a 500 mL 5-necked round-bottom flask equipped with a stainless steel half-moon-shaped stirring blade, a nitrogen inlet tube, a Dean-Stark apparatus equipped with a condenser, a thermometer, and a glass end cap, 20.157 g (0.186 mol) of PPD and 180.000 g of NMP were added, and the temperature in the system was set to 50° C. under a nitrogen atmosphere, and the mixture was stirred at a rotation speed of 200 rpm to obtain a solution.

[0328] To this solution, 54.914 g (0.186 mol) of s-BPDA and 120.000 g of NMP were added all at once, and the mixture was stirred at 50° C. for 5 hours. Then, NMP was added to make the solid content concentration uniform so as to be about 15% by mass, thereby obtaining a varnish containing polyamic acid.

[0329] The obtained varnish was then applied to a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film. The properties and evaluation results of the film are shown in Table 2.

[0330] Comparative Example 6

[0331] In the same manner as in Comparative Example 5, a varnish was obtained.

[0332] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 2.

[0333] Comparative Example 7

[0334] A varnish was obtained in the same manner as in Example 7.

[0335] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 2.

[0336] Comparative Example 8

[0337] A varnish was obtained in the same manner as in Example 8.

[0338] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 2.

[0339] Comparative Example 9

[0340] A varnish was obtained in the same manner as in Example 9.

[0341] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 2.

[0342] Comparative Example 10

[0343] A varnish was obtained in the same manner as in Example 10.

[0344] Then, the obtained varnish was applied on a glass plate by spin coating and kept at 80°C for 20 minutes on a hot plate (step 1). Thereafter, it was kept at 350°C for 15 minutes and 450°C for 10 minutes in a hot air dryer under a nitrogen atmosphere to obtain a polyimide film (step 2). The physical properties and evaluation results of the film are shown in Table 2.

[0345] [Table 1]

[0346] Table 1

[0347]

[0348] *) The numbers of imide and amide parts represent the molar ratio

[0349] [Table 2]

[0350] Table 2

[0351]

[0352] *) The numbers of imide and amide parts represent the molar ratio

[0353] As shown in Table 1, it can be seen that the weight loss of the polyimide film obtained by the manufacturing method of the embodiment from 300°C to 400°C is small, and the imidization reaction and high molecular weight can be fully achieved. In addition, it can be seen that the polyimide film obtained by the manufacturing method of the embodiment can take into account both low yellow index and high tensile elongation. From the above, it can be seen that the manufacturing method of the polyimide film of the present invention can fully achieve the imidization reaction and high molecular weight of the polyimide precursor, and can obtain a polyimide film with high colorless transparency and high elongation and excellent heat resistance.

Claims

1. A method for producing a polyimide film, comprising: Step 1, removing the solvent from a varnish containing a polyimide precursor having a polyamic acid portion and a solvent at 50 to 120° C. and drying the varnish; and Step 2: After maintaining at 300 to 400° C. for 10 to 120 minutes, maintaining at 420 to 500° C. to carry out imidization. The polyamic acid portion has a structural unit derived from tetracarboxylic dianhydride and a structural unit derived from a diamine, and the diamine providing the structural unit derived from the diamine includes a diamine having an ionization potential of 7.10 eV or more.

2. The method for producing a polyimide film according to claim 1, wherein: The polyimide precursor having a polyamic acid portion is at least one selected from the group consisting of polyamic acid and imide-amic acid copolymers.

3. The method for producing a polyimide film according to claim 1 or 2, wherein: The tetracarboxylic dianhydride providing the structural unit derived from tetracarboxylic dianhydride contains tetracarboxylic dianhydride having an electron affinity of 2.5 eV or less.

4. The method for producing a polyimide film according to any one of claims 1 to 3, wherein: The polyimide precursor contains a repeating unit represented by the following formula (1): In formula (1), A 1 A is a tetravalent aromatic group having 4 to 39 carbon atoms, 1 Optionally having at least one selected from the group consisting of -O-, -SO2-, -CO-, -CH2-, -C(CH3)2-, -C2H4O-, -OCO-, -COO-, -NHCO-, -CONH-, and -S- as a bonding group, B 1 is a group represented by the above general formula (2), X 1 , X 2 are each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an alkylsilyl group having 3 to 9 carbon atoms, In formula (2), Y 1 , Y 2 Each independently represents a single bond, a group represented by -COO-, or a group represented by -OCO-, and R 1 , R 2 , R 3 Each independently represents an organic group having 1 to 20 carbon atoms, and h, i, j and k are integers of 0 to 4.

5. The method for producing a polyimide film according to claim 4, wherein: A 1 is a group represented by the following formula (3), 6. The method for producing a polyimide film according to any one of claims 2 to 5, wherein: The imide-amic acid copolymer contains a repeating unit represented by the following formula (4): In formula (4), A 2 is at least one selected from the group consisting of the group represented by the above formula (5) and the group represented by the above formula (6), B 2 is a group represented by the above general formula (2), In formula (2), Y 1 , Y 2 Each independently represents a single bond, a group represented by -COO-, or a group represented by -OCO-, and R 1 , R 2 , R 3 Each independently represents an organic group having 1 to 20 carbon atoms, and h, i, j and k are integers of 0 to 4. 7 . A polyimide film obtained by the production method according to claim 1 .

8. The polyimide film according to claim 7, wherein The weight reduction rate at 300 to 400° C. measured by increasing the temperature from 40° C. to 550° C. at a temperature increase rate of 10° C. / min using a differential thermal thermogravimetric measuring apparatus was 0.2% or less.

9. The polyimide film according to claim 7 or 8, wherein The yellowness index of the polyimide film with a thickness of 10 μm is less than 30, and the tensile elongation of the polyimide film with a thickness of 10 μm is 10% or more when subjected to a tensile test with a test piece size of 10 mm×70 mm and a distance between clamps of 50 mm.

Citation Information

Patent Citations

  • Polyimide precursor, resin composition, and method for producing resin film

    WO2017051827A1